Factor VIII activity of BAY 94‐9027 is accurately measured with most commonly used assays: Results from an international laboratory study. Issue 5 (8th July 2018) - Church, N.; Leong, L.; Katterle, Y.; Ulbrich, H.‐F.; Noerenberg, I.; Kitchen, S.; Michaels, L. A.
Abstract : Introduction: Discrepancies in the measurement of modified factor VIII (FVIII) products have been recognized, highlighting the need for adjustments in clinical laboratory practices to ensure effective monitoring of patients treated with these products, particularly using the one‐stage (activated partial thromboplastin time [aPTT]) assay. Aim: To assess the ability of clinical laboratories to measure the activity of BAY 94‐9027, a PEGylated extended half‐life FVIII product, using routine (predominantly one‐stage) assays in clinical laboratories Methods: Blinded samples of FVIII‐deficient plasma spiked with defined levels of BAY 94‐9027 and a recombinant FVIII product comparator were provided to 52 clinical laboratories that routinely conduct FVIII testing. Samples were provided at 3 concentrations (low, medium and high), and laboratories analysed the samples using routine in‐house one‐stage and, when available, chromogenic assays. Acceptable spiked recovery (accuracy) of the local laboratory methods to measure BAY 94‐9027 was the primary endpoint of the study. Results: Accurate FVIII measurements were obtained at all concentrations for both products using the chromogenic assay and most of the commonly used one‐stage reagents, both ellagic acid and silica based. Two specific silica‐based reagents, APTT‐SP and PTT‐A, underestimated BAY 94‐9027 levels at all concentrations, consistent with previous findings. Conclusions: FVIII activity of BAY 94‐9027 was accurately measured with most commonly used one‐stage assays used in routine clinical practice. The chromogenic assay was also accurate. It is recommended that clinical laboratories identify and avoid specific inappropriate reagents, such as the APTT‐SP and PTT‐A, in their one‐stage assays for FVIII monitoring.